Semiclassical strong-field theory of phase delays in ω-2ω above-threshold ionization - Arbo, Diego (2022)
Phase and time delays of atomic above-threshold ionization were recently experimentally explored in an ω-2ω setting [Zipp, Optica 1, 361 (2014)2334-253610.1364/OPTICA.1.000361]. The phases of wave packets ejected from argon by a strong 2ω pulse were probed as a function of the relative phase of a weaker ω probe pulse. Numerical simulations solving the time-dependent Schrödinger equation (TDSE) displayed a sensitive dependence of the doubly differential momentum distribution on the relative phase between the ω and 2ω fields. Moreover, a surprisingly strong variation of the extracted phase delays on the intensity of the probe pulse was found. We present a semiclassical strong-field description of the phase delays in the emission of electrons in an ω-2ω setting and apply it to atomic hydrogen. Nonperturbative effects in both the 2ω pump and the ω probe field are included. The semiclassical description allows tracing phase delays to path interferences between emission during different points in time of emission within the temporal unit cell of the two-color laser field. We find good agreement between the semiclassical saddle-point approximation, the full strong-field approximation (SFA), and previous results applicable in the perturbative limit of probe fields. We show that the RABBIT-like perturbative description of phase delays breaks down for stronger fields and higher-energy electron emission. In this regime, characterization of the ionization signal requires an entire ensemble of phase delays δi(E) with i=1,2,... the difference in photon numbers of the strong 2ω field involved in the interfering paths. Comparison between SFA and TDSE calculations reveals the influence of the Coulomb field even in this strong-field scenario.